2012
DOI: 10.1111/j.1574-6941.2012.01428.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival characteristics of diarrheagenicEscherichia colipathotypes andHelicobacter pyloriduring passage through the free-living ciliate,Tetrahymenasp.

Abstract: Free-living protozoa have been implicated in the survival and transport of pathogens in the environment, but the relationship between non-Shiga toxin-producing Escherichia coli or Helicobacter pylori and ciliates has not been characterized. Six diarrheagenic pathotypes of E. coli and an isolate of H. pylori were evaluated for their susceptibility to digestion by Tetrahymena, an aquatic ciliate. Tetrahymena strain MB125 was fed E. coli or H. pylori, and the ciliate's egested products examined for viable bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
(52 reference statements)
2
20
0
Order By: Relevance
“…In comparison with the vegetative cells of T. pyriformis, no significant morphological difference in the membrane was noticed after T. pyriformis-C. jejuni coincubation. Our data correlate with previous reports on S. enterica serovar Typhimurium and E. coli, which have no detectable cytotoxic effects on Tetrahymena (33,46,47), in contrast to Acanthamoeba spp., which are killed by other pathogenic bacteria (48)(49)(50)(51).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In comparison with the vegetative cells of T. pyriformis, no significant morphological difference in the membrane was noticed after T. pyriformis-C. jejuni coincubation. Our data correlate with previous reports on S. enterica serovar Typhimurium and E. coli, which have no detectable cytotoxic effects on Tetrahymena (33,46,47), in contrast to Acanthamoeba spp., which are killed by other pathogenic bacteria (48)(49)(50)(51).…”
Section: Discussionsupporting
confidence: 82%
“…The C. jejuni packaged in expelled free MLBs was a little bigger than that in the intracellular vacuoles; the bacteria are mostly rod-shaped, and their size may exceed 2 m, with an average length of 1 m. Here, this phenomenon is probably due to the loosening of MLB membranes after expulsion into the medium, resulting from decreased pressure on the MLBs, compared with that inside the protozoal cell (54). Transmission electron micrographs of E. coli and L. pneumophila contained in MLBs also showed that the bacteria inside food vacuoles of Tetrahymena were smaller than those inside expelled MLBs (47,54).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, it can take many hours of electron microscope time to acquire enough micrographs to analyze, while many low-power fields can be acquired from cells exposed to fluorescence-based viability dyes, even in the short time afforded for image acquisition. While the provided protocols were optimized with N. gonorrhoeae and primary human neutrophils, they can be adapted to assess the viability of many species of gram-negative and gram-positive bacteria in a variety of cell types, including all phagocytic and nonphagocytic eukaryotic cells 5,[15][16][17][18][19][20][21][22][23][24]26 . Bacterial viability dyes provide a powerful experimental tool to examine mechanisms of bacterial pathogenesis in eukaryotic cells and the ability of eukaryotic cells to control bacterial infection.…”
Section: Discussionmentioning
confidence: 99%
“…The protocols outlined in this article were used to assess the viability of N. gonorrhoeae that is attached to and inside primary human neutrophils, including in different populations of neutrophil phagosomes 5,13,14 . However, these protocols can be applied to assess viability of gram-positive and gram-negative bacteria in professional phagocytes, nonprofessional phagocytes, and protozoa [15][16][17][18][19][20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%